Vibration trauma as a causative factor of internal carotid artery dissection - Jaworski, Jacek; Kotuła, Lidia; Budzisz-Turbakiewicz, Dominika; Kądziołka, Kinga; Grabowska–Aleksandrowicz, Katarzyna; Blicharski, Tomasz; Kocki, Janusz; Rejdak, Konrad (Journal of Education, Health and Sport, 2019)
Vibration trauma serves as a potential yet not recognized in large clinical series risk factor of cervical artery dissection. We present case report of a young male patient who developed internal carotid artery dissection as a result of prolonged drilling.